GAMBARAN KEJADIAN DIARE BALITA 6-24 BULAN DAN KONTAMINASI BAKTERI Eshericia coli PADA PENYAJIAN MP ASI LOKAL DI KELURAHAN TANDANG, SEMARANG - Vitiana, Destie Nur Laily; Martini, Martini; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Toddlers are vulnerable to get diarrhea. Consuming contaminated complementary food is one of cause toddler’s diarrhea. Management of complementary food is more susceptible to microbiologycal contamination. This study aims to determine the description of Eshericia coli contamination in serving complementary feeding for 6-24 month toddlers. The other aims are to determine description of Hazard Analisys Critical Control Points (HACCP) factors, food handlers characteristics, and environment sanitation factors to Eshericia coli contamination in serving complementary feeding. This study used surveys and laboratory tests with cross sectional approach. Samples were 84 6-24 month toddlers in Tandang village and samples swab of infant feeding utensil and complementary food were consumed. The results of this study showed 39 (46,4%) swab samples positive for Eshericia coli, and 37 (44%) toddlers were have diarrhea history.